Carbon Nanofibers Modified Graphite Felt for High Performance Anode in High Substrate Concentration Microbial Fuel Cells - Youliang Shen; Yan Zhou; Shuiliang Chen; Fangfang Yang; Suqi Zheng; Haoqing Hou (The Scientific World Journal)
Carbon nanofibers modified graphite fibers (CNFs/GF) composite electrode was prepared for anode in high substrate concentration microbial fuel cells. Electrochemical tests showed that the CNFs/GF anode generated a peak current density of 2.42 mA cm−2 at a low acetate concentration of 20 mM, which was 54% higher than that from bare GF. Increase of the acetate concentration to 80 mM, in which the peak current density of the CNFs/GF anode greatly increased and was up to 3.57 mA cm−2, was seven times as that of GF anode. Morphology characterization revealed that the biofilms in the CNFs/GF anode were much denser than those in the bare GF. This result revealed that the nanostructure in the anode not only enhanced current generation but also could tolerate high substrate concentration.